Application of taxonomy analysis in selection of young sportsman in karate and football - Ajvaz Berisha; Afrim Koca; Kushtrim Berisha (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2019)
The selecting represents the optimal selection of that part of the anthropological status that is important for the success in the respective sport and that meets the specific needs of the athlete and also for the potential athlete's orientation and perfection in terms of certain sports disciplines. Regarding the selection of the working methods in this research, there were selected those methods which are supposed to help in drawing conclusions about the nature of the problem posed. The sample was defined as students aged 12 years from the Middle School "Selami Hallaqi" Gjilan. In this study is included a total of 90 students, that is, two groups of 45 students. The first group is consisted of students who besides regular hours of physical education 2 times a week also exercised karate two more times a week by one hour per day. The second group comprised of students who besides regular hours of physical education 2 times a week, also exercised football two more times per week, by an hour a day. Measurements were made at the end of the school year. 9 motor variables were applied (Kurelić et al., 1975), running in 20 meters (MT20V), the long jump from the place (MSKDM), high jump from the place (MSKVM), hand taping (MTRUK), leg taping ( MTNOG), eight with bowing (MOSPR), running sideways (mtrs) bowing ahead in the bank (MFLPRK), legs spread apart-retaliation (MFLSP). For the processing of the results it was applied the t-test analysis for independent samples. The basic statistical parameters of the results obtained from the students involved in the research show that the values obtained do not have an outlined asymmetry and incline to the lowest (hypo cortical). Taxonomic analysis shows that were obtained applying two groups of students divided by motor skills and gained distinction in these variables between groups is statistically significant. The second taxonomy of the motor skills shows that from the 90 students, young sportsmen involved in research, 56 of them can be defined as a student athlete with high motor skills to perform motor movements with explosive character which are well coordinated in time and space, with a top speed of movement segment. Motor dimensions of the explosive strength, speed segment, coordination and flexibility are important motor skills for success in a big number of sports (Findak et al., 1992; Popović, 1998).